Dilemmas with brand management in clusters - Barbara Szymoniuk (Polityki Europejskie, Finanse i Marketing)
One of the basic marketing problems which have been revealed in Polish clusters` practice is the issue of brand management. Dilemmas and problems of the shared responsibility for the image appear, are related to the necessity of reconciling the interests of various members of the cluster (in the sphere of image and tax issues), including the members who own their own trademarks; the interests of the territory and the environment the cluster originates from, as well as of institutions funding the development of clusters from aid funds from the European Union. A basic problem is encountered already on the stage of making the decision concerning the name of the cluster’s market brand. The majority of clusters in Poland, created as a result of implementing European Union’s projects, have long and complicated names, which are at times difficult to memorise. Even though those names perform their function in the processes of applying for, realizing and controlling the project, they do not fulfill the conditions set for good market brands. Another dilemma of brand management in clusters is related to the issue of granting the trademark to cluster participants and ensues from the Polish tax law. In the case of clusters operating as a business enterprise and sharing the trademark for money, the situation with tax law seems to be clear; however, it is more complicated when a cluster functions as a non-profit association which, additionally, does not wish to be registered as a VAT payer. A further dilemma of brand policy in clusters is also connected with the legal protection of the trademark in the case of realizing European Union projects. From the point of view of the purchasers of the cluster’s offer, an additional brand management problem is an excessive number of trademarks and labels on the packages of the products and in marketing messages of clusters. This causes a considerable information chaos. The problems described in the present article are based on both positive and negative experiences of Polish clusters, especially those offering foodstuffs. The source of knowledge of these experiences is a series of publications by the Polish Agency for Enterprise Development issued in 2010-2012, the experiences of the author resulting from her long work in clusters, as well as telephone in-depth interviews with the coordinators of foodstuff clusters.